Lao People's Democratic Republic : 2019 Article IV Consultation-Press Release; Staff Report; Statement by the Executive Director for Lao People's Democratic Republic. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Lao People's Democratic Republic (P.D.R) analyses that after more than a decade of high growth with low inflation, country is solidifying its progress toward graduating from the Least Developed Country (LDC) status. However, more than one-fifth of the population remains poor, regional disparities are persistent, and recurring natural disasters pose risks for poverty reduction. A large current account deficit, low level of reserves, a high level of debt, managed exchange rate, and a dollarized banking system amplify macro-vulnerabilities. The authorities recognize the current economic challenges and their comprehensive reform programs aim at rebalancing the economy from a resource based to a more diversified growth model by investing in human development and improving competitiveness. Modernizing monetary governance and building reserves supported by greater exchange rate flexibility will help to mitigate external shocks in an uncertain global environment.